Jordan Left Derivation and Jordan Left Centralizer of Skew Matrix Rings - H.Majeed, Abdul Rahman; C.Shaheen, Rajaa (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
In this paper, we determine the form of Jordan left derivation and Jordan Left Centralizers of a Skew matrix ring over a ring R .